Analisis Waktu Tunggu Pelayanan Foto Thorax pada Pasien Rawat Jalan - Anugrah, M David; Fatimah, Mustika; Novitre, Ayu; Anisah, Anisah (Poltekkes Kemenkes Semarang, 2024)
Background: The time between the patient's arrival and the testing findings is known as the waiting time for the results of a x-ray chest. The amount of time patients must wait to receive medical care from a health service unit, it also reflects how the hospital handles service components that are customized to the needs and demands of patients in public hospitals. This study aims to determine the suitability of waiting time for outpatient chest x-ray services with the standard of Indonesia Ministry of Health No.129/Menkes/SK/II/2008.Methods: The type of research used in this paper is qualitative by using the case study for analyzing the waiting time of x-ray chest in outpatients.Results: Eight patients, or 16% of the total had waiting time of three hours or more. Out of all patients, 84% or 42 patients had a waiting period of less than three hours. 22 minutes is the quickest waiting time, while 5 hours 56 minutes is the late waiting time. Such that in outpatients, the typical wait time for a x-ray chest picture is one hour and thirty minutes.Conclusions: Siloam Sriwijaya Hospital Palembang in adjusting the Minimum Service Standards the Hospital has met the minimum service standards of the Decree of the Minister of Health No. 129/Menkes/SK/II/2008 that the waiting time for a chest photo is â‰¤ 3 hours.